GENERAL CHARACTERISTICS OF THE FLUTTER AND ITS INFLUENCE ON THE STABILITY OF THE AIRCRAFT - Kuvvatali Rakhimov Ortikovych; Ogiloy Khakimova Ilhomjon qizi; Azizbek Samijonov Ismoiljon ugly (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article explores the general characteristics of the flutter phenomenon and its effect on aircraft stability in flight. The main goal of this work study the main problems of the mechanics of composite materials, problems of the aerospace industry, such as deformation, durability, vibration and dynamic stability of structures made of composite materials.